A Rare Case of Cerebral Venous Sinus Thrombosis Following the Second Dose of BNT162b2 mRNA COVID-19 Vaccine—Just a Coincidence? A Case Report - David Matyáš; Roman Herzig; Libor Šimůnek; Mohamed Abuhajar (Reports)
Background and Clinical Significance: The occurrence of cerebral venous sinus thrombosis (CVST), both with or without thrombocytopenia, following COVID-19 vaccination, is well documented and more common in recipients of vector vaccines. Cases of CVST following immunization with the COVID-19 messenger RNA (mRNA) vaccine are rare; most of these cases occur within 28 days of the first dose of the vaccine. Case Presentation: We present the case of a 38-year-old male with a history of two episodes of deep vein thrombosis in the lower limbs, but without a specific thrombophilic condition, who developed CVST 13 days after the second dose of the Pfizer/BioNTech BNT162b2 vaccine. He suffered from diffuse tension-type headache of progressively increasing intensity, and his objective neurological findings were normal. Magnetic resonance venography showed thrombosis of the transverse and right sigmoid sinuses, and magnetic resonance imaging (MRI) of the brain revealed no cerebral infarction. Two months later, a follow-up MR venography showed partial recanalization of the affected sinuses, and a brain MRI showed no infarction. Conclusions: Given the temporal sequence and the absence of other possible causes, we speculate that the second dose of the COVID-19 BNT162b2 vaccine may have triggered the development of CVST.